2003
DOI: 10.1016/s0195-668x(02)00807-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ezetimibe, a new cholesterol absorption inhibitor, on plasma lipids in patients with primary hypercholesterolemia

Abstract: Ezetimibe, which significantly reduces LDL-C and favorably affects other lipid variables, may provide a well tolerated and effective new option for lipid management in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(67 citation statements)
references
References 12 publications
1
58
0
1
Order By: Relevance
“…The very significant decrease of triglycerides observed in our patients was due to fibrate action; it should however be noted that some studies on non-HIV patients found a limited, but statistically significant decrease of triglycerides during ezetimibe monotherapy [19,20]. We also observed a significant increase in HDL cholesterol, which has already been described during ezetimibe monotherapy in studies on non-HIV patients; this HDL increase has been connected to the greater increase in concentration of apolipoprotein A-I with ezetimibe compared to placebo [1922]. …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The very significant decrease of triglycerides observed in our patients was due to fibrate action; it should however be noted that some studies on non-HIV patients found a limited, but statistically significant decrease of triglycerides during ezetimibe monotherapy [19,20]. We also observed a significant increase in HDL cholesterol, which has already been described during ezetimibe monotherapy in studies on non-HIV patients; this HDL increase has been connected to the greater increase in concentration of apolipoprotein A-I with ezetimibe compared to placebo [1922]. …”
Section: Resultssupporting
confidence: 68%
“…Both efficacy and safety of ezetimibe monotherapy as well as of ezetimibe+statin coadministration have been widely demonstrated in dyslipidemic non-HIV patients [1622]: ezetimibe monotherapy reduced LDL cholesterol by 17–20% compared with placebo, triglycerides levels also decreased significantly by 5% and HDL cholesterol increased by 2–3%. Furthermore, studies on HIV+ patients showed that ezetimibe is as effective as statin monotherapy in decreasing cholesterol, is well tolerated and does not interact with HAART [2325].…”
Section: Introductionmentioning
confidence: 99%
“…Ezetimibe (Zetia) is an FDA approved hypocholesterolemic drug that blocks cholesterol absorption from the intestine by interfering with the bona fide gut cholesterol transporter NPC1L1 107-109 . Inhibition of cholesterol absorption by ezetimibe also causes LDL receptor levels to increase, thereby facilitating removal of cholesterol from the circulation.…”
Section: Cholesterol Targeting and Prostate Healthmentioning
confidence: 99%
“…Ezetimibe lowered LDL-C by 17-18% 1)2)3)4). However, LDL-C was reduced by 25-27% when ezetimibe was added to an on-going statin therapy 8)9)10)14).…”
Section: Discussionmentioning
confidence: 99%
“…Ezetimibe, an inhibitor of intestinal cholesterol absorption, lowers the low density lipoprotein-cholesterol (LDL-C) by 17-18% 1)2)3)4). However, ezetimibe elevates the activity of 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase resulting in the increase of cholesterol synthesis 5)6)7).…”
Section: Introductionmentioning
confidence: 99%